Hubungan Antara Posisi Kerja dan Usia dengan Keluhan Muskuloskeletal pada Nelayan - Oksfriani Jufri Sumampouw; Gloria Joseph (HEALTH CARE : JURNAL KESEHATAN, 2022)
Introduction: Musculoskeletal complaints contribute as much as 43-58% of all occupational diseases in the world, including workers in fisheries such as fishermen. Musculoskeletal complaints can occur due to multifactorial. The work posture and age are factors that cause musculoskeletal complaints in fishermen. The purpose of this study was to determine the correlation between work posture and age with musculoskeletal complaints in fishermen in Kalasey Satu Village, Mandolang Minahasa District. Method: This research was conducted in Kalasey Satu Village, Mandolang Minahasa Sub-district in August-December 2021. The respondents of this research were 36 fishermen. The variables in this study were age, work posture, and musculoskeletal complaints. The instruments used are the Nordic Body Map (NBM) questionnaire to measure musculoskeletal complaints and the Ovako Work Analysis System (OWAS) to measure work posture. In addition, stationery, cameras and computers are used. Data analysis was carried out univariately and bivariately. Results: The results showed that the work posture and musculoskeletal complaints are not significantly related (Asympt. Sig = 0.148). Furthermore, respondents aged > 45 years were mostly in the category of very high musculoskeletal complaints as many as 17 respondents (47.2%) whereas respondents aged 45 years and under were mostly in the category of high musculoskeletal complaints as many as 11 respondents (30.6%) . The results of statistical tests obtained the Asympt. Sig value = 0.003 (< 0.05) which means age and musculoskeletal complaints are significantly related where respondents aged > 45 years have a risk of 12.467 times experiencing very high musculoskeletal complaints when compared to respondents aged 45 years and under. Conclusion: It can be concluded that age is associated with musculoskeletal complaints in fishermen in Kalasey Satu Village, Mandolang District. Therefore, fishermen must work in an ergonomic position and further research is needed on the factors that cause other musculoskeletal complaints in fishermen.